2017
DOI: 10.1007/s40430-017-0913-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and implementation of a force control strategy for drilling operations with an industrial robot

Abstract: In this paper, a theoretical and experimental study to evaluate the use of force control in drilling operations, based on an industrial robot, is presented. A force control strategy embedded in a commercial industrial robot, originally devoted to general machining tasks, is adapted to drilling operations. It is shown that satisfactory results can be achieved in standard industrial applications. Unwanted displacements can occur, resulting in dimensional uncertainty, especially in specimens with very small dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Similar research can be found in the work of Klimchik A. et al [24], but they used the stiffness model proposed by Pashkevich A. et al, [12]. In the case of drilling process control, we found the works of Garnier S. et al [25] and Gomes D. et al [18], both emphasized that the control of the process should be carried out in three phases; the first contact or indent phase, the material removal phase and the final contact phase. The first work realized a theoretical model estimating the force of each phase and thus compensating the trajectory.…”
Section: Control Of the Machining Processsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar research can be found in the work of Klimchik A. et al [24], but they used the stiffness model proposed by Pashkevich A. et al, [12]. In the case of drilling process control, we found the works of Garnier S. et al [25] and Gomes D. et al [18], both emphasized that the control of the process should be carried out in three phases; the first contact or indent phase, the material removal phase and the final contact phase. The first work realized a theoretical model estimating the force of each phase and thus compensating the trajectory.…”
Section: Control Of the Machining Processsupporting
confidence: 77%
“…Specifically, we will find force controls, force/position controls and impedance controls. These control types are used with adaptive, robust, intelligent or classical control methods or techniques [18].…”
Section: Control Of the Machining Processmentioning
confidence: 99%
“…Qin et al [134] developed a robot drilling system, in which two accelerometer sensors were used to obtain the vibration signals of the EE which was analysed to calculate the location and orientation errors. Rosa et al [135] developed a force control strategy to enhance the application possibility of robot drilling. The method was used to improve drilling quality by assuring the thrust force, and to reduce the sliding during the first contact between the twist drill and the workpiece.…”
Section: Monitoring and Compensationmentioning
confidence: 99%
“…On the other hand, modern industrial robots are characterized by flexibility of applications, large working spaces and low cost. However, their constructive characteristics like low stiffness and complexity of programming lead to disadvantages compared to conventional CNC machine tools [10][11][12][13][14][15][16][17][18]. Robot structure stiffness modeling and analysis, synthesis and control in machining tasks are in the focus of interest among many researchers [11,12,14,15,[19][20][21][22].…”
Section: Outline Of the Conceptmentioning
confidence: 99%